1) ![x^{2}-y^{2}=(x+y)(x-y) x^{2}-y^{2}=(x+y)(x-y)](https://tex.z-dn.net/?f=x%5E%7B2%7D-y%5E%7B2%7D%3D%28x%2By%29%28x-y%29)
=======================================================
2) ![c^{2}-25=(c+5)(c-5) c^{2}-25=(c+5)(c-5)](https://tex.z-dn.net/?f=c%5E%7B2%7D-25%3D%28c%2B5%29%28c-5%29)
=======================================================
3) ![25-a^{2}=(5+a)(5-a) 25-a^{2}=(5+a)(5-a)](https://tex.z-dn.net/?f=25-a%5E%7B2%7D%3D%285%2Ba%29%285-a%29)
=======================================================
4) ![m^{2}-n^{2}=(m+n)(m-n) m^{2}-n^{2}=(m+n)(m-n)](https://tex.z-dn.net/?f=m%5E%7B2%7D-n%5E%7B2%7D%3D%28m%2Bn%29%28m-n%29)
=======================================================
5) ![b^{2}-0,04=(b+0,2)(b-0,2) b^{2}-0,04=(b+0,2)(b-0,2)](https://tex.z-dn.net/?f=b%5E%7B2%7D-0%2C04%3D%28b%2B0%2C2%29%28b-0%2C2%29)
=======================================================
6) ![n^{2}-\frac{4}{9}=(n+\frac{2}{3})(n-\frac{2}{3}) n^{2}-\frac{4}{9}=(n+\frac{2}{3})(n-\frac{2}{3})](https://tex.z-dn.net/?f=n%5E%7B2%7D-%5Cfrac%7B4%7D%7B9%7D%3D%28n%2B%5Cfrac%7B2%7D%7B3%7D%29%28n-%5Cfrac%7B2%7D%7B3%7D%29)
=======================================================
7) ![100-p^{2}=(10+p)(10-p) 100-p^{2}=(10+p)(10-p)](https://tex.z-dn.net/?f=100-p%5E%7B2%7D%3D%2810%2Bp%29%2810-p%29)
=======================================================
8) ![a^{2}-1=(a+1)(a-1) a^{2}-1=(a+1)(a-1)](https://tex.z-dn.net/?f=a%5E%7B2%7D-1%3D%28a%2B1%29%28a-1%29)
=======================================================
9) ![49-b^{2}=(7+b)(7-b) 49-b^{2}=(7+b)(7-b)](https://tex.z-dn.net/?f=49-b%5E%7B2%7D%3D%287%2Bb%29%287-b%29)
=======================================================
10) ![m^{2}-400=(m+20)(m-20) m^{2}-400=(m+20)(m-20)](https://tex.z-dn.net/?f=m%5E%7B2%7D-400%3D%28m%2B20%29%28m-20%29)
=======================================================
11) ![1,21-x^{2}=(1,1+x)(1,1-x) 1,21-x^{2}=(1,1+x)(1,1-x)](https://tex.z-dn.net/?f=1%2C21-x%5E%7B2%7D%3D%281%2C1%2Bx%29%281%2C1-x%29)
=======================================================
12) ![\frac{25}{64}-p^{2}=(\frac{5}{8}+p)(\frac{5}{8}-p) \frac{25}{64}-p^{2}=(\frac{5}{8}+p)(\frac{5}{8}-p)](https://tex.z-dn.net/?f=%5Cfrac%7B25%7D%7B64%7D-p%5E%7B2%7D%3D%28%5Cfrac%7B5%7D%7B8%7D%2Bp%29%28%5Cfrac%7B5%7D%7B8%7D-p%29)